A Novel Non‐enzymatic Selective and Sensitive Glucose Sensor Based on Nickel‐Copper Oxide@3D‐rGO/MWCNTs. Issue 2 (11th September 2020) - Taji, Zahra; Ensafi, Ali A.; Heydari‐Soureshjani, Elahe; Rezaei, Behzad
Abstract: In this work, a modified 3D‐rGO/MWCNT with nickel and copper oxide nanoparticles were synthesized. The structural properties of this nanocomposite were investigated by several techniques. The fabricated sensor at optimum condition potential of +0.60 V ( vs . Ag/AgCl) and a rotational rate of 1800 rpm gave a detection limit of 0.04 μmol L −1 with two dynamic ranges of 0.10–300 and 300–900 μmol L −1 glucose with high stability. The good accuracy of the fabricated sensor was proved in the determination of glucose in a blood sample (with recoveries between 95 % to 105 % and RSDs of 1.2 to 2.5 %). Abstract :